A computational study of the non-adiabatic coupling among low-lying doublet states of the CN radical. (December 2021) - Terashkevich, V.A.; Pazyuk, E.A.; Stolyarov, A.V.
Highlights: The spin-orbit, radial and Coriolis coupling electronic matrix elements are calculated among low-lying doublet states of CN from first principles. The second order Van Vleck correction for the fine structure of the A 2 Π and B 2 Σ + states is estimated. The impact of the excited states manifold on the fine structure of the A ∼ B complex is small, excepting the Λ -doubling constant q A . The ab initio functions could be useful for a global deperturbation treatment of the CN A ∼ B ∼ X complex on a spectroscopic level of coincidence. Graphical abstract: Abstract: First principle electronic structure calculations on low-lying doublet states of the CN radical have been performed using the multi-reference configuration interaction method and large all-electron basis sets. Beside the adiabatic interatomic potentials, the non-adiabatic spin-orbit and L -uncoupling electronic matrix elements were evaluated for the mutually perturbed (2) B 2 Σ + ∼ (1–4) 2 Π and (1) A 2 Π ∼ (1–3) 2 Σ +, (1) 2 Σ −, (1, 2) 2 Δ pairs of states. The radial coupling matrix element was calculated between the X 2 Σ + and B 2 Σ + states. The reliability of the derived A ∼ X and A ∼ B matrix elements was confirmed by comparison with their empirical counterparts. Both local and regular perturbations in the A ∼ B ∼ X complex were found to depend mostly on spin-orbit and electronic-rotational interactions between the lowest A 2 Π, and B 2 Σ + states. Excited states, in all their diversity, have little effect on the fine structure of the A ∼ B complex, except for the qA Λ-doubling function. The ab initio coupling functions can be crucial to providing a global deperturbation treatment for the A, B and X states on a spectroscopic level of accuracy.